Gas permeation properties of the matrimid based carbon tubular membrane: the effect of carbonization temperature - Sazali, N. (2015)
Carbon membranes produced from the carbonization of polymeric materials is a promising candidate for gas separation, as it offers good permeability-selectivity combination exceeding polymeric membranes. Carbon membranes are particularly useful in gas separation, and excellent separation could be achieved even between gases with almost similar molecular size. In this study, tubular supported carbon membrane was prepared using Matrimid 5218 as polymeric precursor. The polymer solution was coated on the surface of tubular support by using dip-coating method. In order to produce a high quality carbon membrane, the effect of carbonization temperature on the gas permeation properties was studied. The polymer tubular membrane was carbonized under Argon atmosphere at different carbonization temperature of 600, 750, and 850 °C. Pure gas permeation tests were performed using CO2 and N2 at room temperature with pressure 8 bars. Based on the results, the highest CO2/ N2 selectivity of 79.69 was obtained for carbon membrane prepared at 850 °C. High carbonization temperature is necessary to break down the functional group of polymeric precursor into carbon material. An ideal carbon membrane carbonized at optimum temperature would possess high separation properties with high crystalline, density and compactness.